Multiphase fluid flow solver and its application to multidimentional problems - Jakušev, Aleksandr; Starikovičius, Vadimas (Lietuvos matematikos rinkinys, 2004)
Modelling of fluid flow in porous media plays an important part in many applications. The authors have created extensible software package (the solver) for this task, using object-oriented approach. After a short introduction to the problems aimed by this solver, the solver is described, followed by the results of benchmarking and numerical solution of Buckley–Leverett 2-D problem.
Keywords: porous media; multiphase flow; numerical modelling; OOP; Buckley–Leverett